2021
DOI: 10.7759/cureus.16037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anxiety, Depression, and Perceived Stigma in Healthcare Workers in Nepal During Later Phase of First Wave of COVID-19 Pandemic: A Web-Based Cross-Sectional Survey

Abstract: IntroductionThe COVID-19 pandemic has caused discrimination and social stigma among healthcare workers (HCW) causing psychological problems due to prolonged work shifts, uncertain pay, lack of personal protective equipment (PPE), added fear of infection to self or family, and so on. This online survey is directed towards the determination of anxiety, depression, and stigma among healthcare providers in Nepal during the later phase of the first wave of the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 18 publications
3
50
1
1
Order By: Relevance
“…Contrary to our second hypothesis, this study found that cancer participants were less stressed and had better eudemonic psychological wellbeing, coping better (1 in 2 flourishing), with higher positive affect and less negative affect and with higher psychological flexibility than those without cancer. The levels of stress cancer patients experienced in this study were also lower than those of frontline healthcare workers found in a recent study [ 77 ]. This interesting finding may again be related to individuals who have had a cancer experience developing the abilities to better deal with new health-related threats compared to those who had never before experienced such threat.…”
Section: Discussioncontrasting
confidence: 76%
“…Contrary to our second hypothesis, this study found that cancer participants were less stressed and had better eudemonic psychological wellbeing, coping better (1 in 2 flourishing), with higher positive affect and less negative affect and with higher psychological flexibility than those without cancer. The levels of stress cancer patients experienced in this study were also lower than those of frontline healthcare workers found in a recent study [ 77 ]. This interesting finding may again be related to individuals who have had a cancer experience developing the abilities to better deal with new health-related threats compared to those who had never before experienced such threat.…”
Section: Discussioncontrasting
confidence: 76%
“…For example, one study 81 found that HCWs who stay in a hostel or accommodations provided by a hospital report higher perceived stigma than those who stay at home. Another study 80 found that HCWs living with the elderly, who are more prone to infection 86 , report higher perceived stigma. However, two studies found no difference in perceived stigma between living with family or not 84,85 .…”
Section: The Stigmatizedmentioning
confidence: 97%
“…It is noteworthy that though some scholars suggest that female HCWs may be more vulnerable to stressful environments and more prone to feeling stigmatized 82 , other studies found a null association between gender and perceived stigma 80,81,83,84,85 .…”
Section: The Stigmatizedmentioning
confidence: 97%
See 1 more Smart Citation
“…Generalized Anxiety Disorder (GAD-7) B : 7-item assessment of anxiety symptoms, structured in the same format as the PHQ-9. Previously used in Nepal [99][100][101]. PT T0,T1,T2 .…”
Section: Accurate Diagnosis Structured Clinical Interview For Dsm-5-c...mentioning
confidence: 99%